Extent of resection affects prognosis for patients with glioblastoma in non-eloquent regions. (October 2020) - Kow, Chien Yew; Kim, Bernard J.H.; Park, Thomas I-H; Chen, Joseph C.C.; Vong, Chun Kiet; Kim, Joo Yeun; Shim, Vickie; Dragunow, Mike; Heppner, Peter
Highlights: Within a comparable population of glioblastoma, GTR and EoR are factors for survival. A minimum of 74% EoR is required to achieve improved survival. Incremental increases from 74% continues to improve survival rates. Maximal safe resection remains the standard of care for surgical treatment. Abstract: Glioblastoma (GBM) is a malignant cerebral neoplasm carrying poor prognosis. The importance of extent of resection (EoR) in GBM patient outcomes has been argued in the literature. Previous studies included tumors in eloquent regions of the brain. This confounds the role of EoR by including patients with intrinsically worse outcomes but will be over-represented in the reduced EoR category. In a homogenous group of patients in whom GTR was considered achievable, we investigated the effect of increasing EoR on survival. A retrospective review of 51 patients was undertaken. Quantitative, volumetric analysis of pre-operative and post-operative magnetic resonance image was compared with corresponding clinical details. The primary outcome measured was post-operative overall survival. Median overall survival was 18.3 months for GTR patients compared to 11.6 months for non-GTR ( p = 0.025). Median pre-operative contrast-enhancing tumor volume for GTR patients was 54.7 cm 3 and 24.9 cm 3 for non-GTR. Post-operative median residual tumor volume was 1.1 cm 3 in the non-GTR cohort. In multivariate analyses, GTR (HR [95% CI] = 0.973 [0.954–0.994], p = 0.00559) and increasing EoR (HR [95% CI] = 0.964 [0.944–0.985], p = 0.000665) remained predictors of survival. Centile dichotomization of EoR revealed 74% (HR [95% CI] = 0.351 [0.128–0.958], p = 0.0409) as the lowest threshold conferring statistically significant survival benefit. Where technically feasible, both GTR and EoR remained as independent prognostic factors for survival. GTR remains the gold standard for surgical treatment of GBM in patients, 74% being the minimum EoR required to confer survival benefit.